The Impact of budgeting and budgetary control on performance of Great Zimbabwe University - Makamanzi, Anockstage (Midlands State University, 2017)
The study sought to analyze the impact of budgeting and budgetary control systems being incorporated at Great Zimbabwe University. Great Zimbabwe University is a state-owned institution which has been defied with adverse variances for the past three years up to date. The study revealed that these adverse variances was as a result of the nature of a poor budgeting system currently employed by the organization. The researcher used a descriptive research design and GZU as a case study in this research. A sample of twenty respondents was selected using a judgmental sampling approach. Gathering of data with the aim of confirming the existence of a problem was done through the use of questionnaires and interviews. Twenty out of twenty respondents filled and returned the questionnaires and three respondents were interviewed. The gathered data was presented and analysed in the form of graphs, tables and pie charts. Moreover, the gathered information was interpreted and compared to the existing literature in an attempt to confirm the existence of the problem. The results showed that there is inflexible budget structure, lack of lower level participation in budget process, poor supervision from management and ineffective implementation of budgets. The research recommends that the organization should adopt a flexibility budget structure, allow participation of low level managers in budget processes and effective implementation of budgets. The research strives to unleash that the budgeting approach used by the organisation has some loopholes which gave rises to unfavourable variances. Other budget techniques like zero based budgeting was surfaced so that the organization may adopt in order to curb the recurrence of adverse variances.